Up regulated expression of tumour necrosis factor α converting enzyme in peripheral monocytes of patients with early systemic sclerosis. Issue 8 (12th July 2005) - Bohgaki, T; Amasaki, Y; Nishimura, N; Bohgaki, M; Yamashita, Y; Nishio, M; Sawada, K-i; Jodo, S; Atsumi, T; Koike, T
Abstract : Background: Systemic sclerosis (SSc) is accompanied by abnormalities in humoral and cellular immune systems. Objective: To determine the genes specifically expressed in the immune system in SSc by analysis of the gene expression profile of peripheral blood mononuclear cells (PBMC) from patients with SSc, including those treated with haematopoietic stem cell transplantation (HSCT). Additionally, to investigate the clinical significance of the up regulation of tumour necrosis factor α (TNFα) converting enzyme (TACE). Methods: PBMC from patients with SSc (n = 23) and other autoimmune diseases (systemic lupus erythematosus (SLE, n = 16), rheumatoid arthritis (RA, n = 29)), and from disease-free controls (n = 36) were examined. Complementary DNA arrays were used to evaluate gene expression of PBMC, in combination with real time quantitative polymerase chain reactions. TACE protein expression in PBMC was examined by fluorescence activated cell sorter (FACS). Results: In patients with SSc 118 genes were down regulated after HSCT. Subsequent comparative analysis of SSc without HSCT and healthy controls indicated SSc-specific up regulation for three genes: monocyte chemoattractant protein-3 (p = 0.0015), macrophage inflammatory protein 3α (p = 0.0339), and TACE (p = 0.0251). In the FACS analysis, TACE protein was mainly expressed on CD14 + monocytes both in patients with SSc and controls. TACE expression on CD14 + cells was significantly increased in patients with early SSc (p = 0.0096), but not in those with chronic SSc, SLE, or RA. TACE protein levels in SSc monocytes correlated with the intracellular CD68 levels (p = 0.0016). Conclusions: Up regulation of TACE expression was a unique profile in early SSc, and may affect the function of TNFα and other immunoregulatory molecules.